Transmission of 100-Gb/s VSB DFT-Spread DMT Signal in Short-Reach Optical Communication Systems - Fan Li; Xinying Li; Junwen Zhang; Jianjun Yu (IEEE Photonics Journal, 2015)
In this paper, we experimentally demonstrated transmission of a 100-Gb/s discrete Fourier transform (DFT)-spread 32-quadrature amplitude modulation (QAM) discrete multitone (DMT) signal in an intensity-modulation/direct-detection system utilizing a direct-modulated laser. We find that DFT-spread cannot only reduce the peak-to-average power ratio but also improve the robustness to high-frequency power attenuation and narrow-band interference in the high-speed short-reach optical communication systems. Vestigial sideband (VSB) enabled by a narrow-bandwidth tunable optical filter can be adopted to resist the power fading effect induced by the fiber chromatic dispersion after direct detection. The measured bit error ratio (BER) of 100-Gb/s VSB DFT-spread DMT signal after 20-km large effective area fiber is less than the hard-decision forward-error-correction (HD-FEC) limitation of $3.8 × 10^{-3}$ .